ELEMENTARY SCHOOL TEACHERS' BELIEFS ABOUT MATHEMATICAL PROBLEM-SOLVING: A CASE STUDY IN PINRANG REGENCY - Irianto Aras; Turmudi; Tatang Herman (Mathematics Education and Application Journal (META), 2025)
Teachers’ beliefs about students’ mathematical problem-solving abilities substantially influence the nature of problem-solving instruction provided in classrooms. This study aims to describe elementary school teachers’ beliefs about mathematical problem-solving, focusing on their understanding of the nature of problem-solving, its importance, and how it should be taught. Six elementary school teachers with diverse teaching experiences and grade levels participated in the study through semi-structured and in-depth interviews. The findings reveal four significant insights: (1) Teachers generally define problem-solving as solving calculation-based tasks using specific procedures grounded in students’ mathematical knowledge; (2) Most teachers perceive mathematical problem-solving tasks merely as “difficult problems” for students, without recognizing their non-routine characteristics; (3) Teachers believe the primary difficulties students face involve understanding problems and determining appropriate procedures; and (4) Classroom instruction tends to emphasize providing examples of correct solution procedures as fixed models students must follow. Overall, the analysis shows that although teachers acknowledge the importance of problem-solving, their understanding remains limited regarding diverse problem-solving strategies and the deeper conceptual meaning of “problem” in mathematical problem-solving.   Keywords: Teachers' Beliefs, Mathematical Problem-Solving, Elementary School   Pentingnya keyakinan guru mengenai kemampuan pemecahan masalah matematika sangat berdampak bagi pembelajaran pemecahan masalah yang mereka lakukan di kelas. Penelitian ini bertujuan untuk mendeskripsikan keyakinan guru Sekolah Dasar tentang kemampuan pemecahan masalah matematika yang menyangkut sifat pemecahan masalah matematika, pentingnya pemecahan masalah, dan pengajaran pemecahan masalah matematika. Penelitian ini diikuti oleh 6 orang guru SD dengan pengalaman mengajar dan tingkatan kelas yang berbeda dengan melakukan wawancara semi terstruktur dan mendalam. Hasil penelitian menunjukkan empat temuan utama: (1) Para guru mengartikan pemecahan masalah adalah menyelesaikan soal perhitungan dengan prosedur tertentu menggunakan pengetahuan matematika yang dimiliki siswa, (2) Sebagian besar guru memandang soal pemecahan masalah matematika adalah soal yang sulit dikerjakan oleh siswa tanpa menyebutkan kriteria non rutin, (3) Guru meyakini bahwa kesulitan utama siswa terletak pada aspek memahami masalah dan menentukan prosedur yang tepat, dan (4) Pengajaran pemecahan masalah di kelas cenderung terfokus pada pemberian contoh prosedur penyelesaian yang benar sebagai acuan yang harus diikuti oleh siswa dalam pemecahan masalah. Analisis keseluruhan menunjukkan bahwa guru meyakini pentingnya pemecahan masalah matematika, meskipun demikian pemahaman mereka masih terbatas tentang strategi pemecahan masalah yang variatif dan makna mendalam tentang arti masalah dalam pemecahan masalah matematika.   Kata kunci: Keyakinan Guru, Pemecahan Masalah Matematika, Sekolah Dasar.